Incidence and factors associated with mortality of neonatal sepsis - I Made Kardana (Paediatrica Indonesiana, 2011)
Background Neonatal sepsis is one of the major causes of mortality and long term morbidity in neonates, particularly in prematureÂ and low birth weight infants. The incidence of neonatal sepsisÂ varies from 1 to 4 in 1000 live births in developed countries andÂ 10 to 50 in 1000 live births in developing countries. The mortality rate of neonatal sepsis remains high, especially in developingÂ countries.Objective To describe the incidence, mortality rate, and factorsÂ associated 'With mortality in neonatal sepsis in Sanglah Hospital,Â Denpasar.Methods A retrospective, cohort study was conducted in the Perinatology Ward, Department of Child Health, Sanglah Hospital,Â Denpasar, Bali from January to December 2008. One hundredÂ thirtyô€„eight patients 'With neonatal sepsis were enrolled in thisÂ study. Patients' characteristic data were collected including sex,Â mode of delivery (spontaneous, nonô€„spontaneous), condition atÂ birth (vigorous, asphyxic), gestational age (premature, full tenn),Â birth weight Â«2500 grams, > 2500 grams), and sepsis classificaô€„tion (early onset sepsis, late onset sepsis). Outcomes were groupedÂ into alive and dead.Results A total of 138 cases of neonatal sepsis were reviewed,Â 59.4% of whom were boys, 63.0% spontaneously delivered,39.1 %Â asphyxic, 53.6% 'With low birth weight, 50.7% premature, and84.8% with early onset sepsis. The incidence of neonatal sepsisÂ was 5% of babies admitted, 'With a mortality rate of 28.3%. LowÂ birth weight and prematurity were significantly associated withmortality in neonatal sepsis (RR8.4, 95% CI 2.4 to 29.0, P = 0.001Â and RR3.4, 95% ClI.O to 11.0, P ô€€‚ 0.042, respectively).Â Conclusion The incidence of neonatal sepsis in SanglahÂ Hospital was 5% of babies admitted, with a mortality rate ofÂ 28.3%. Low birth weight and prematurity were significantly associated with mortality in neonatal sepsis.Â 2011;51:144-8].